The effect of perceived stress on depression in college students: The role of emotion regulation and positive psychological capital - Liu, Yafei; Yu, Haibo; Shi, Yaohui; Ma, Chao (Frontiers in Psychology, 2023)
Introduction College students have become a high prevalence group and vulnerable group of depression. The present study aims to explore the effect of perceived stress on depression in a sample of Chinese college students and proposes that both emotion regulation and positive psychological capital play a moderating role between the two, so as to provide rational intervention for the prevention of potential depression among college students. Method In this study, 1,267 college students (46.4% female) from a university in western China were selected for the study using a whole-group convenience sampling method. Results After controlling for gender, this study found that both cognitive reappraisal and positive psychological capital positively moderated the relationship between perceived stress and depression, and both significantly inhibited depression in high and low stress perceivers, and the inhibitory effect was more pronounced in high stress perceivers, but expression inhibition did not moderate the relationship between perceived stress and depression. Discussion The results suggest that college students can be helped to cope with the negative effects of perceived stress on depression by increasing the frequency of their use of cognitive reappraisal strategies and encouraging the accumulation of positive psychological capital. This study provides theoretical and practical implications for rational interventions for depression among college students.